(untitled) (Scientific journal of the Fergana State University, 2024)
Listening comprehension is one of the skills that foreign language learners acquire in addition to speaking, reading and writing. However, there are still many students who have difficulty learning to listen. The purpose of this study is to determine the problems that students face when mastering listening skills in the department of foreign languages of technical universities. The information in this article was collected from students of the Department of Foreign Languages of the Karshi Engineering and Economic Institute. Research shows that there are six additional listening skills that students frequently struggle with.